Strategi Coping pada Mantan Penganut Aliran Sesat - Putri, Khairunnisa; Kushartati, Sri (Unisia, 2018)
This study aims to find out about the coping strategies on the former follower of a cult and the factors that influence them. Two respondents participated in this study. The method in this study uses a qualitative method with a phenomenological approach. The results of this study indicate that the two respondents perform coping strategy to reduce pressure felt. They use emotional focused coping in the form of distancing, escape avoidance, self-control, accepting responsibility, positive reappraisal, and denial. Planfull problem solving is used as a form of problem-focused coping. Known to both the subject of coping processes that vary in shape using coping strategies influenced by physical health factors, problem solving skills, and social skills.